The Art of Packaging the Sperm Genome: Molecular and Structural Basis of the Histone-To-Protamine Exchange - Moritz, Lindsay; Hammoud, Saher Sue (Frontiers in Endocrinology, 2022)
Male fertility throughout life hinges on the successful production of motile sperm, a developmental process that involves three coordinated transitions: mitosis, meiosis, and spermiogenesis. Germ cells undergo both mitosis and meiosis to generate haploid round spermatids, in which histones bound to the male genome are replaced with small nuclear proteins known as protamines. During this transformation, the chromatin undergoes extensive remodeling to become highly compacted in the sperm head. Despite its central role in spermiogenesis and fertility, we lack a comprehensive understanding of the molecular mechanisms underlying the remodeling process, including which remodelers/chaperones are involved, and whether intermediate chromatin proteins function as discrete steps, or unite simultaneously to drive successful exchange. Furthermore, it remains largely unknown whether more nuanced interactions instructed by protamine post-translational modifications affect chromatin dynamics or gene expression in the early embryo. Here, we bring together past and more recent work to explore these topics and suggest future studies that will elevate our understanding of the molecular basis of the histone-to-protamine exchange and the underlying etiology of idiopathic male infertility.